2004
DOI: 10.1152/ajpheart.00479.2003
|View full text |Cite
|
Sign up to set email alerts
|

Ventricular gradient and nondipolar repolarization components increase at higher heart rate

Abstract: .-Differences in action potential duration reflect differences in ion channel properties. These properties also determine rate dependence of action potential duration, and transmural dispersion was confirmed experimentally to increase with cycle length. While several electrocardiographic indexes characterizing repolarization abnormalities have been proposed, studies of their heart rate dependence are missing. This study therefore investigated rate relationship of two repolarization descriptors, namely, the so-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
36
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 47 publications
3
36
4
Order By: Relevance
“…In the report of Smetana et al long-term ECG recordings had been obtained, thus providing larger RR ranges than those obtained when recording only short term 10-second resting ECGs. In addition, Smetana et al showed that Twave parameters mainly change for RR intervals shorter than 700 ms. 8 Of note, the heart rate influences on T-wave morphology parameters based on PCA are much lesser than observed for the crude QT duration (>10% with R 2 = 39% in our study). Our data suggest that for RR intervals included between 900 and 1200 ms a correction for heart rate changes is not mandatory for T-wave morphology parameters analysis.…”
Section: Significance Of T-wave Morphologycontrasting
confidence: 68%
See 4 more Smart Citations
“…In the report of Smetana et al long-term ECG recordings had been obtained, thus providing larger RR ranges than those obtained when recording only short term 10-second resting ECGs. In addition, Smetana et al showed that Twave parameters mainly change for RR intervals shorter than 700 ms. 8 Of note, the heart rate influences on T-wave morphology parameters based on PCA are much lesser than observed for the crude QT duration (>10% with R 2 = 39% in our study). Our data suggest that for RR intervals included between 900 and 1200 ms a correction for heart rate changes is not mandatory for T-wave morphology parameters analysis.…”
Section: Significance Of T-wave Morphologycontrasting
confidence: 68%
“…8 In the present study, the slopes of the relationships between heart rate and PCA parameters are small (≤6 * 10 −3 ) although significant, explaining only 5-10% of the distribution of the parameters (Table 6). It is smaller than in the reports from Smetana et al 8 the discrepancy being probably related to the range of heart rate considered. In the report of Smetana et al long-term ECG recordings had been obtained, thus providing larger RR ranges than those obtained when recording only short term 10-second resting ECGs.…”
Section: Significance Of T-wave Morphologycontrasting
confidence: 54%
See 3 more Smart Citations